ChemInform Abstract: Oxidative Trifluoromethylthiolation and Thiocyanation of Amines: A General Approach to N—S Bond Formation. Issue 35 (August 2016) - Xiong, Heng‐Ying; Pannecoucke, Xavier; Besset, Tatiana
Abstract: A practical and efficient one‐pot oxidative trifluoromethylthiolation of primary and secondary amines under mild conditions is presented.